2020
DOI: 10.1111/jcal.12508
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the dots: Understanding the interrelated impacts of type, quality and children's awareness of design features and the mathematics content learning goals in digital math games and related learning outcomes

Abstract: This study focused on an examination of how type, quality and children's awareness of design features in digital math games, along with an awareness of the mathematics goals of the game, were related to learning outcomes. We conducted a parallel conversion mixed methods study with 45 students in Grades 3 and 4 (ages 9–10). Students participated in clinical interviews using three digital math games. The results suggest a moderated mediation relationship in which the quality of the design features moderated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Overall, prior research (Ainsworth, 1999; De Bock et al, 2017; Duval, 2006; Goldin, 2003; Hurst et al, 2020; Lesh, 1981; Lesh et al, 1987) revealed the importance of external representations for mathematical learning, but most of these previous studies focused on a conventional learning setting. Recently, research on the field of external representations for mathematical problem solving in DGBL is increasing (Bullock et al, 2021; Duval, 2017; Hung et al, 2014; Moyer-Packenham et al, 2019; 2021), but still scarce.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, prior research (Ainsworth, 1999; De Bock et al, 2017; Duval, 2006; Goldin, 2003; Hurst et al, 2020; Lesh, 1981; Lesh et al, 1987) revealed the importance of external representations for mathematical learning, but most of these previous studies focused on a conventional learning setting. Recently, research on the field of external representations for mathematical problem solving in DGBL is increasing (Bullock et al, 2021; Duval, 2017; Hung et al, 2014; Moyer-Packenham et al, 2019; 2021), but still scarce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research (Bullock et al, 2021; Ke & Clark, 2020; Moyer-Packenham et al, 2019; 2021) suggested that interactions with well-structured MERs in DGBL could enhance students’ abilities to construct a mental model for mathematical problem solving. Specifically, DGBL provides opportunities of translations (i.e., transformations) among different mathematical representations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations